The Reporting Delay Of Acquisition Of Companies In The Post Merger Notification System According To The Law Of Business Competition In Indonesia - Sabirin, Ahmad (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2022)
The implementation of post-merger notification in Indonesia makes it very difficult for the reporting itself and the finances of business actors. For that, the authors recommend that the implementation of the pre-merger notification is a good thing to be implemented in Indonesia, where the pre-merger notification system has been tested in several countries in the United States, Australia, Japan, South Korea, and Germany as well as several ASEAN member countries, such as Thailand, Singapore and the Philippines. Thus, business actors wishing to merge have made prior reports and notifications to KPPU, so that in conducting assessment, monitoring and supervision can prevent monopolistic practices and unfair business competition. As far as possible, this will provide many advantages and efficiency both for business actors and for KPPU in conducting monitoring and supervision due to the practice of mergers.